Analyzing the Combined Role of Good Governance and GDP on Women Literacy in African Countries - Himel, Mohammad (Jurnal Ilmu Ekonomi Terapan, 2024)
Most African countries have been affected due to economic crises regarding hyperinflation and lower agricultural productivity, civil war, lower infrastructural and transportation systems, social and domestic violence, food insecurity due to bad agricultural systems, social and religious inequality, mismanagement of governing systems with defective bureaucracy, environmental degradation and lower practice for sustainable development. In this paper, the author tries to find out two research objectives i) To measure the good governing variables on women literacy between East and West African countries ii) To measure the joint impact of good governance and GDP level between these two countries. The author uses secondary dataset from The World Bank site on quantitative analysis where the author uses multiple regression model for general regression and integrated regression model. At the time of multiple regression (Model 1), GDP, IF, P.S., R.Q. has a positive connection with women literacy for EAC. On the contrary, PHR, FLF, DOFC, R.L. create a negative effect on women's literacy in EAC. But in (Model 2), if the good governance variable connects with GDP for long-lasting development, (GDP*PS), (GDP*RQ) has positive connection with W.L. in EAC. Reversely, L.E., PHR, G.E., R.Q., CC has positive and significant impact in WAC where these variables enhance women literacy to be improved at significant rate (Model 3) where DOFC and EFC has reverse connection with W.L. In spite of case, if GDP connects with good governance variables, (GDP*RQ) and (GDP*PS) has positive connectivi-ty with W.L. in WAC. Policy makers should highlight to promote effective R.L. and G.E. to improve macroeconomic development in EAC where governments of WAC should focus on R.L. and G.E. to ensure women empowerment and social security for sustainable development. Establishing good governance's variables in African countries is carrying need to ensure women empowerment, lessening gender inequality, ensuring women safeness and sustainable development etc.